Kajian Gender dalam Pendidikan Islam dan Transformasi Pendidikan Berkeadilan Gender - Nuridin, Nuridin; Sumarna, Cecep; Rozaq, Abd (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
Discrimination in education whether we realize it or not, it will be very detrimental to oneparty, in this case, women as a party are always number two. There are a number of factorsthat influence the occurrence of discrimination or injustice, namely structural and culturalfactors. (Ariefa, 2008) In addition to development policies that are less gender sensitive, thereare also cultural practices that are gender biased in society. Facing conditions like this, ofcourse, real efforts are needed in efforts to promote women towards education that is moregender-equitable. This study aims to reveal gender differences in equitable Islamic education